2017
DOI: 10.1016/j.jpainsymman.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Home-Based Palliative Care for Children With Incurable Cancer: Long-term Perspectives of and Impact on General Practitioners

Abstract: ContextAlthough a large percentage of children with advanced-stage cancer die at home, remarkably little information is available regarding the experience of general practitioners (GPs) with respect to providing home-based palliative care to children with incurable cancer. ObjectivesTo explore the perspectives of GPs who care for children with advanced-stage cancer in a homebased setting. MethodsIn this cross-sectional study, 144 GPs who provided home-based palliative care to 150 children with incurable cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Of these physical symptoms, fatigue was the most difficult to treat and if/when treated, interventions are likely to be unsuccessful. These findings have been well documented (Lopes et al, 2016;van der Geest et al, 2017). In fact, fatigue is often associated with pain and dyspnea though causal inferences cannot be made; the biological mechanisms of fatigue, pain, and dyspnea may be comparable and likely occur in parallel with disease progression (Okuyama et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Of these physical symptoms, fatigue was the most difficult to treat and if/when treated, interventions are likely to be unsuccessful. These findings have been well documented (Lopes et al, 2016;van der Geest et al, 2017). In fact, fatigue is often associated with pain and dyspnea though causal inferences cannot be made; the biological mechanisms of fatigue, pain, and dyspnea may be comparable and likely occur in parallel with disease progression (Okuyama et al, 2008).…”
Section: Discussionmentioning
confidence: 84%
“…Symptom distress is associated with poor HRQoL in children with advanced cancer (Snaman et al, 2018). Poor perception of children's HRQoL and suboptimal symptom management at EOL is associated with parental grief, depression (McCarthy et al, 2010;Meert et al, 2011;van der Geest et al, 2014;van der Geest et al, 2017), and parental distress after children's death (Rosenberg et al, 2013). Targeted and effective symptom management underscores the complexity of symptom burden and concerted efforts to improve pediatric palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…24 In another study, general practitioners (GPs) providing home-based palliative care reported receiving insufficient information from the hospital about symptoms and difficulties during the palliative phase. 72 Similarly, after a review of patient cases, Houlahan and colleagues 43 identified barriers including a lack of available physicians as reported by nurses, difficulty in obtaining orders for medication and delays in obtaining medication from pharmacy. Disagreement and conflict about treatment decisions and goals were identified as other symptom management barriers.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…However, the emotional impact of a child dying of cancer is enormous both for the GP and the family. 19 Although it happens rarely during a GP's career, it is a memorable event. 19 Continuity of care and facilitated collaboration between hospital and primary care, and between primary healthcare professionals, are essential.…”
Section: Resultsmentioning
confidence: 99%
“…19 Although it happens rarely during a GP's career, it is a memorable event. 19 Continuity of care and facilitated collaboration between hospital and primary care, and between primary healthcare professionals, are essential. A consultation-based contact with a specialised palliative care team to support the GP can be helpful.…”
Section: Resultsmentioning
confidence: 99%